ROS‐Responsive Polyprodrug Nanoparticles for Triggered Drug Delivery and Effective Cancer Therapy. Issue 33 (6th July 2017) - Xu, Xiaoding; Saw, Phei Er; Tao, Wei; Li, Yujing; Ji, Xiaoyuan; Bhasin, Sushant; Liu, Yanlan; Ayyash, Dana; Rasmussen, Jonathan; Huo, Marc; Shi, Jinjun; Farokhzad, Omid C.
Abstract : The application of nanoparticles (NPs) to drug delivery has led to the development of novel nanotherapeutics for the treatment of various diseases including cancer. However, clinical use of NP‐mediated drug delivery has not always translated into improved survival of cancer patients, in part due to the suboptimal properties of NP platforms, such as premature drug leakage during preparation, storage, or blood circulation, lack of active targeting to tumor tissue and cells, and poor tissue penetration. Herein, an innovative reactive oxygen species (ROS)‐responsive polyprodrug is reported that can self‐assemble into stable NPs with high drug loading. This new NP platform is composed of the following key components: (i) polyprodrug inner core that can respond to ROS for triggered release of intact therapeutic molecules, (ii) polyethylene glycol (PEG) outer shell to prolong blood circulation; and (iii) surface‐encoded internalizing RGD (iRGD) to enhance tumor targeting and tissue penetration. These targeted ROS‐responsive polyprodrug NPs show significant inhibition of tumor cell growth both in vitro and in vivo. Abstract : An innovative reactive oxygen species (ROS)‐responsive and tumor‐penetrating polyprodrug nanoplatform for targeted cancer therapy is developed. This nanoplatform can respond to intracellular ROS with a chain‐breakage patterned release of intact anticancer drug, leading to significant inhibition of tumor growth. This new platform can be of high interest for on‐demand delivery of other therapeutic drugs for effective cancer treatment.